2018
DOI: 10.1111/omi.12241
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis inhibits M2 activation of macrophages by suppressing α‐ketoglutarate production in mice

Abstract: Reprograming of metabolic pathways is critical in governing the polarization of macrophages into classical proinflammatory M1 or alternative anti-inflammatory M2 phenotypes in metabolic diseases, such as diabetes. Porphyromonas gingivalis, a keystone pathogen of periodontitis, causes an imbalance in M1/M2 activation, resulting in a hyperinflammatory environment that promotes the pathogenesis of periodontitis. However, whether P. gingivalis infection modulates metabolic pathways to alter macrophage polarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 29 publications
0
29
1
Order By: Relevance
“…However, M2, or alternatively activated macrophages, generally associated with wound healing and tissue repair, are also found within periodontal tissues 73,74 . P. gingivalis is associated with M1 polarization and hyperinflammation, 75 but the lipopolysaccharide has been shown to support M2 polarization 74 . T. forsythia supports an M2 phenotype and has been associated with a delayed macrophage response 76,77 .…”
Section: Discussionmentioning
confidence: 99%
“…However, M2, or alternatively activated macrophages, generally associated with wound healing and tissue repair, are also found within periodontal tissues 73,74 . P. gingivalis is associated with M1 polarization and hyperinflammation, 75 but the lipopolysaccharide has been shown to support M2 polarization 74 . T. forsythia supports an M2 phenotype and has been associated with a delayed macrophage response 76,77 .…”
Section: Discussionmentioning
confidence: 99%
“…All experimental protocols were approved by the Animal Use and Care Committee of Tongji University. Isolation and culture of murine bone marrow‐derived macrophages (BMDMs) are described in our published study 28 . Briefly, 6‐8 week‐old female C57BL/6 mice were sacrificed, and both tibiae and femurs were collected.…”
Section: Methodsmentioning
confidence: 99%
“…Whether P. gingivalis-LPS has this capacity is not known. P. gingivalis causes an imbalance in M1/ M2 activation in macrophages, resulting in a hyperinflammatory environment that promotes the pathogenesis of periodontitis [78]. These authors reported that P. gingivalis or P. gingivalis-derived LPS-induced inflammatory responses enhanced M1 macrophages and suppressed M2 macrophages, even in the presence of IL-4.…”
Section: Activation By Lipopolysaccharidementioning
confidence: 99%
“…LPS [ 4 , 76 ] P.g . causes imbalance in the M1/M2 phenotype of microglia [ 78 ] Leptomeningeal cells P.g . LPS stimulated transfer of inflammatory signals from peripheral macrophages to brain-resident microglia [ 83 , 84 ] Administration of P.g .…”
Section: Aimmentioning
confidence: 99%